Nurses' Experiences on Gender: A Phenomenological Study - Ipek Turhan; Kubra Akcan; Oktay Bektas; Mehmet Dolanbay (CV. Literasi Indonesia, 2023)
This study aimed to reveal gender-related deficiencies by examining nurses' experiences with gender and to guide these deficiencies in further studies. The study used the transcendental model of phenomenology design from the qualitative research method. The present study prefers the criterion sampling included in the purposeful sampling The study group consisted of five female and five male nurses who worked in a state hospital and had gender experiences. The meetings were recorded and carried out face-to-face with the consent of the participants. According to the research results, a theme named gender was determined. Under this theme, 10 categories and two subcategories were identified. The current study concluded that the gender perceptions of nurses were positive, but they exhibited a traditional approach to the roles given to women and men. They did not receive sufficient education on social gender skills. The authors suggested that gender education should be added to the Women's Health and Diseases Nursing course contents.